2015
DOI: 10.1002/2014jd022958
|View full text |Cite
|
Sign up to set email alerts
|

A new dynamical downscaling approach with GCM bias corrections and spectral nudging

Abstract: To improve confidence in regional projections of future climate, a new dynamical downscaling (NDD) approach with both general circulation model (GCM) bias corrections and spectral nudging is developed and assessed over North America. GCM biases are corrected by adjusting GCM climatological means and variances based on reanalysis data before the GCM output is used to drive a regional climate model (RCM). Spectral nudging is also applied to constrain RCM-based biases. Three sets of RCM experiments are integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 41 publications
2
68
0
Order By: Relevance
“…However, it may also degrade global predictions over certain areas in certain situations by amplifying biases in the global fields due to insufficient resolution and/or errors from inappropriate physics (Srinivas et al , ). To demonstrate the added values at the different stages of the adopted methodology, we computed various error statistics following Xu and Yang () and presented them in Table . The error statistics are computed between the observations and NCEP FNL data; WRF 30 km downscaled data; 10 km downscaled data and the 10 km assimilative data for the year 2009.…”
Section: Resultsmentioning
confidence: 99%
“…However, it may also degrade global predictions over certain areas in certain situations by amplifying biases in the global fields due to insufficient resolution and/or errors from inappropriate physics (Srinivas et al , ). To demonstrate the added values at the different stages of the adopted methodology, we computed various error statistics following Xu and Yang () and presented them in Table . The error statistics are computed between the observations and NCEP FNL data; WRF 30 km downscaled data; 10 km downscaled data and the 10 km assimilative data for the year 2009.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies revealed that noticeable biases still exist in the GCM products due to their relatively coarse spatial resolution, particularly at regional or local scale (Ines & Hansen, 2006;Xu & Yang, 2015). However, several studies revealed that noticeable biases still exist in the GCM products due to their relatively coarse spatial resolution, particularly at regional or local scale (Ines & Hansen, 2006;Xu & Yang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these deficiencies, the dynamical downscaling technique has been widely used in regional climate studies (Oh et al, 2014;Wang and Kotamarthi, 2015;Xu and Yang, 2015). Dynamical downscaling uses initial conditions (ICs) and boundary conditions (BCs) from global models to drive regional models for high-resolution simulations.…”
Section: Introductionmentioning
confidence: 99%